2015
DOI: 10.1002/jcc.23862
|View full text |Cite
|
Sign up to set email alerts
|

Probing the reactivity of microhydrated α‐nucleophile in the anionic gas‐phase SN2 reaction

Abstract: To probe the kinetic performance of microsolvated α-nucleophile, the G2(+)M calculations were carried out for the gas-phase S(N)2 reactions of monohydrated and dihydrated α-oxy-nucleophiles XO(-)(H2O)(n = 1,2) (X = HO, CH3O, F, Cl, Br), and α-sulfur-nucleophile, HSS(-)(H2O)(n = 1,2), toward CH3Cl. We compared the reactivities of hydrated α-nucleophiles to those of hydrated normal nucleophiles. Our calculations show that the α-effect of monohydrated and dihydrated α-oxy-nucleophiles will become weaker than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Usually, the study [4q,5b] of α‐effect compares HOO − (H 2 O) n with HO − (H 2 O) n , where the solvent molecules are the same. Here we found, although the solvent molecules differ, the comparison between HOO − (H 2 O) n=1‐3 and HO − (HOOH)(H 2 O) n‐1 also suggests that α‐effect exists.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, the study [4q,5b] of α‐effect compares HOO − (H 2 O) n with HO − (H 2 O) n , where the solvent molecules are the same. Here we found, although the solvent molecules differ, the comparison between HOO − (H 2 O) n=1‐3 and HO − (HOOH)(H 2 O) n‐1 also suggests that α‐effect exists.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the effect of solvents on chemical reactions is a central subject in chemistry. Gas-phase studies of microsolvated ions provide a means to investigate the role of individual solvent molecules and may shed light on the transition between gas-phase and condensed-phase reactivity. , The ion–molecule nucleophilic substitution (S N 2) reaction is a fundamental organic reaction. Numerous experimental and computational studies on microsolvated S N 2 reactions revealed that individual solvent molecules have multiple influences on the reaction, , including reduced reactivity, , altered reaction dynamics, complex reaction mechanisms, and the enhanced α-effect. …”
mentioning
confidence: 99%
“…The HOO – anion is an α-nucleophile, possessing a lone pair-bearing electron adjacent to the α-position O atom, and HO – is its corresponding normal nucleophile. When α-nucleophiles display enhanced nucleophilicity relative to normal nucleophiles of similar basicity, ,,, the term α-effect was used to describe this deviation in reactivity relative to that expected from Brønsted-type correlations …”
Section: Resultsmentioning
confidence: 99%